Viscous anisotropy of textured olivine aggregates: 2. Micromechanical model. Issue 10 (25th October 2016) - Hansen, Lars N.; Conrad, Clinton P.; Boneh, Yuval; Skemer, Philip; Warren, Jessica M.; Kohlstedt, David L.
Abstract: The significant viscous anisotropy that results from crystallographic alignment (texture) of olivine grains in deformed upper mantle rocks strongly influences a large variety of geodynamic processes. Our ability to explore the effects of anisotropic viscosity in simulations of these processes requires a mechanical model that can predict the magnitude of anisotropy and its evolution. Unfortunately, existing models of olivine textural evolution and viscous anisotropy are calibrated for relatively small deformations and simple strain paths, making them less general than desired for many large‐scale geodynamic scenarios. Here we develop a new set of micromechanical models to describe the mechanical behavior and textural evolution of olivine through a large range of strains and complex strain histories. For the mechanical behavior, we explore two extreme scenarios, one in which each grain experiences the same stress tensor (Sachs model) and one in which each grain undergoes a strain rate as close as possible to the macroscopic strain rate (pseudo‐Taylor model). For the textural evolution, we develop a new model in which the director method is used to control the rate of grain rotation and the available slip systems in olivine are used to control the axis of rotation. Only recently has enough laboratory data on the deformation of olivine become available to calibrate these models. We use these new data to conduct inversions for the best parameters to characterize both the mechanical and textural evolution models. These inversions demonstrate that the calibrated pseudo‐Taylor model best reproduces the mechanical observations. Additionally, the pseudo‐Taylor textural evolution model can reasonably reproduce the observed texture strength, shape, and orientation after large and complex deformations. A quantitative comparison between our calibrated models and previously published models reveals that our new models excel in predicting the magnitude of viscous anisotropy and the details of the textural evolution. In addition, we demonstrate that the mechanical and textural evolution models can be coupled and used to reproduce mechanical evolution during large‐strain torsion tests. This set of models therefore provides a new geodynamic tool for incorporating viscous anisotropy into large‐scale numerical simulations. Key Points: A micromechanical model is developed for estimating the viscous anisotropy of olivine aggregates A companion model is developed to predict the evolution of olivine crystal orientations at very large strains Both models are calibrated with recent experimental results, yielding new tools to be incorporated into large‐scale geodynamics models